CURRICULUM VS REALITY : MEASURING THE EFFECTIVENESS OF ENTREPRENEURSHIP EDUCATION IN CREATING ASPIRING ENTREPRENEURS - Rosmiati, Neni; Rema Mulyani; Ilhamsyah; Rahman, Abdul; Gusyaeri, Muhammad; Nadhira, Elsa; Siva S, Neng; Adam M, M. Cahya (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study aims to analyze the influence of entrepreneurship education on entrepreneurial interest among students at Lingga Buana PGRI University Sukabumi. Entrepreneurship is a key driver of economic growth and job creation, thus higher education institutions need to optimize entrepreneurship education to foster students' entrepreneurial interest. This research employs a quantitative approach with descriptive and correlational design. The population consists of students who have taken entrepreneurship courses, with a sample of 300 respondents selected using proportionate stratified random sampling technique. The research instrument is a structured questionnaire using a 5-point Likert scale that has been tested for validity and reliability. Data analysis technique uses simple linear regression analysis with SPSS version 25 software. The results show that entrepreneurship education has a positive and significant effect on students' entrepreneurial interest with a correlation coefficient (R) of 0.721 and coefficient of determination (R²) of 0.520. This means that 52% of the variation in entrepreneurial interest can be explained by entrepreneurship education. Descriptively, entrepreneurship education received a "Good" rating (mean = 3.78) and students' entrepreneurial interest was in the "High" category (mean = 3.92). This research provides an important contribution to developing more effective entrepreneurship education strategies in higher education institutions.